Welfare Policy of Professors and Academic Excellence for National Development in Nigerian Universities: Cost Implication Analysis - Azende, Terungwa; Iorpev, Luper; Ayoor, Ivungu John (European Journal of Sustainable Development, 2019)
This paper is to explore the relationship between welfare of professors and academic excellence in Nigerian universities for national development with emphasis on cost implications. A survey design was adopted for this study. Pearson Correlation was used in analyzing the collected data to test whether or not there is any relationship between one set of variable and another. Findings reveal that lack of welfare for professors have a significant and negative influence on academic excellence and cost management in Nigerian universities. This paper recommends that universities should have a clear and standing policy on welfare of professors and other academic staff so as to enhance academic excellence and also save cost in running the university. Keywords: Welfare Policy, Nigerian Universities, Professors, Cost Implication